Construction of Chinese Judicial Power from the Perspective of National Governance. (2nd July 2016) - Deyong, Shen; Shibing, Cao; Xinzhou, Shi
Abstract: The Chinese national governance system includes the Party's governing system, the People's Congress system, the administrative system, the court system and the procuratorate. Judicial power is neutral, passive, independent and final, features that reflect the irreplaceable nature of its role in national governance. The growth of judicial power is diachronic, complex and evolutionary, which means that its construction will be a tortuous and difficult process. Given the limitations of the functions of judicial power in China and their immediate results, we should fix our gaze on the construction of a socialist country under the rule of law and the optimization of the structure and functions of our national governance system by taking checks and balance as the principle in the allocation of judicial power, taking rights protection as the heart of the operation of judicial power, taking harmonious operation as the standard for guaranteeing judicial power, and cultivating legal culture as the foundation supporting judicial power. In optimizing national governance itself, we should strengthen its functions of adaptation, integration, goal attainment and latency.